Performance Appraisal with Management By Objective - Hani Damayanti Aprilia; Ulan Alna Sari; Claricha Ignez Pratiwi Mukti; Fenny Saptiani; Akgis Cahya Ningtias (Indonesian Association for Public Administration (IAPA), 2022)
This study aims to analyze the performance appraisal and follow-up plan of the results of the performance appraisal. This research was conducted in Bandar Lampung, with the object of research on Sigerhub Lampung. This research is a case study research with a qualitative approach. Data collection techniques with structured interviews, observations, and documentation. Technical data analysis using interactive model data analysis developed by Miles &huberman. The results showed that Sigerhub conducted performance assessments for both permanent employees, freelance employees and interns. Performance appraisals are carried out on a weekly and monthly basis, by the immediate supervisor combined with 360 Degree Feedback. Performance appraisal using the Management By Objective method. The follow-up plan of the results of the performance assessment is carried out by providing promotions and or rewards, reprimands both verbally and in writing both to permanent employees, freelance employees and interns.